RESPONSIVE LAW MODEL FOR REALIZING FOOD SOVEREIGNTY REGENCY - Ade Arif Firmansyah; Yhannu Setyawan; Malicia Evendia (Constitutional Law Society, 2022)
Data from the Ministry of Agrarian and Spatial Planning/National Land Agency in 2018 showed that the raw area of rice fields in Indonesia was only 7.1 million hectares (ha) or down compared to 2013 which was still 7.75 million hectares. This will of course have a negative impact onthe achievement of national food sovereignty vsi, coupled with the condition of regional agricultural regulations which are still sectoral and not comprehensive. By using a doctrinal approach, this paper aims todevelop a responsive legal model to create a food-sovereign district. The results of the study indicate that a responsive legal model to empower farmers and create food sovereignty districts is needed because so far regional regulations in the agricultural sector are still partial so that they have not fully supported the realization of the condition of food sovereignty. The targets to be realized, the scope of regulation, the scope, and direction of the regulation model of a responsive law-based food sovereignty district will contain three major parts, namely: the Agricultural Land Protection Division, the Farmer Protection and Empowerment Division, and the Irrigation Network Section, so that the realization of a sovereign district is realized. food can be achieved comprehensively.